1981
DOI: 10.1159/000250289
|View full text |Cite
|
Sign up to set email alerts
|

Eine ungewöhnliche Form von bullöser Mucinose der Haut bei Hashimoto-Thyreoiditis

Abstract: A female patient developed a severely irritating papulous dermatosis localized on the face and arms, running a chronic course. Histology displayed blister formation and mucin deposits in the corium. Laboratory determinations showed antibodies against thyroglobulin and cytoplasmic antibodies with high titers; thyroid function tests were normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Papular or vesicular eruptions of mucinous lesions have been reported in conjunction with Hashimoto's thyroiditis [9,10], In spite of the elevated antimicrosomal antibodies, such a disease could not be proved in our patient, and his skin lesions manifested themselves in another way.…”
Section: Discussioncontrasting
confidence: 55%
“…Papular or vesicular eruptions of mucinous lesions have been reported in conjunction with Hashimoto's thyroiditis [9,10], In spite of the elevated antimicrosomal antibodies, such a disease could not be proved in our patient, and his skin lesions manifested themselves in another way.…”
Section: Discussioncontrasting
confidence: 55%
“…6 The association with thyroid disease was further supported by Schuppli et al when he described a female with normal T 3 and T 4 levels but with high titres of antithyroid antibodies. 8 Other authors believe focal mucinosis to be solely reactive. Others have suggested that focal mucinosis is the result of a dysfunction of broblasts in a localized area.…”
Section: Discussionmentioning
confidence: 99%